APPLICATION OF THE NUMBERED HEADS TOGETHER LEARNING MODEL WITH VIRTUAL LABORATORY SUPPORT ON WRITTEN COMMUNICATION - Joko Wahyu Setyono; Azhar Azhar; Imam Mahadi (Physics Education Study Program, Faculty of Education and Teacher Training, UNSIQ, 2024)
Science education is now adapting to 21st-century skills. One rarely implemented stage is the ability of students to communicate in writing because the lack of attention given by teachers. This study addresses the issue of how the implementation, whether there are differences, and the improvement of cooperative learning model type NHT assisted by virtual laboratories affect written communication on the topic of simple machines for eighth-grade junior high school students. This research aimed to investigate the implementation of the NHT learning model supported by virtual laboratory tools in improving written communication skills. The research method used is descriptive quantitative research, employing a quasi-experimental design, specifically the matching only posttest group design. The study was conducted at Class VIII of State Junior High School 5 Tandun. The sample consists of two eighth-grade classes: Class VIII-1 with 23 students as the experimental group and Class VIII-2 with 23 students as the control group.. The results of the study revealed that the overall average score for all aspects in the NHT class with virtual laboratory support was 88%, indicating a